Cryogenic Air A Potential Solution 'Io The Problem Of Respirable Mine Dust - L. K. Eigenbrod (Society for Mining, Metallurgy & Exploration, 1971)
Throughout the mining industry, pneumoconiosis is one of the most severe occupational health problems being faced. The goal of completely eliminating pneumoconiosis as an occupational health hazard was underscored by the Federal Government with its enactment of Public Law 91-173 (Federal Coal Mine Health and Safety Act of 1969). Under this law, permissible dust level standards will be placed at 2 mg/m3 in mine atmospheres by December 30, 1972. The mining industry is thus faced with the tremendous technical challenge of achieving this level. Two basic questions can be raised with regard to this legislation. First, does a maximum dust concentration of 2 mg/m3 prevent the occurrence of pneumoconiosis? Secondly, can this dust standard be achieved using presently available methods and equipment? A precise answer to the first question has not yet been developed by the medical profession. Studies are continuing on the origin, prevention, and therapy of pneumoconiosis, and permissible dust levels could become even lower as medical evidence accumulates. The mining industry has addressed itself to the problems of dust con-tro1 for many years as related to personnel health, explosive mixtures, visibility, and machinery damage. Dust control methods being employed involve